plantDARIO: web based quantitative and qualitative analysis of small RNA-seq data in plants - Patra, Deblina; Fasold, Mario; Langenberger, David; Steger, Gerhard; Grosse, Ivo; Stadler, Peter F. (Frontiers in Plant Science, 2014)
High-throughput sequencing techniques have made it possible to assay an organism’s entire repertoire of small non-coding RNAs (ncRNAs) in an efficient and cost-effective manner. The moderate size of small RNAseq datasets makes it feasible to provide free web services to the research community that provide many basic features of a small RNA-seq analysis including quality control, read normalization, ncRNA quantification, and the prediction of putative novel ncRNAs. DARIO is one such system that so far has been focussed on animals. Here we report on the extension of this system to plant short non-coding RNAs (sncRNAs), which includes modifications to cope with plant-specific ncRNA processing. The current version of plantDARIO covers analyses of mapping files, RNA-seq quality control, expression analyses of annotated ncRNAs, prediction of miRNAs and snoRNAs from unknown expressed loci, and expression analyses of user-defined loci for Arabidopsis thaliana, Beta vulgaris, and Solanum lycopersicum. It links to a visualization browser for custom track display. The easy-to-use platform of plantDARIO quantifies RNA expression based on annotated ncRNAs from different ncRNA databases and also some ncRNA annotations validated by our group. The plantDARIO web site can be accessed at http://plantdario.bioinf.uni-leipzig.de/.